Identifikasi dan Karakteristik Morfologi Jamur Makroskopis di Garis Wallace dan Weber Kawasan Hutan Jalur Pendakian Moya Mabuku Kota Ternate Menggunakan Koordinat GPS - Mutimanda Dwisatyadini; Hikmah Zikriyani; Susi Sulistiana; Inggit Winarni; Nurmaya Papuangan; Nurhasanah Nurhasanah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Differences in organic matter content and soil pH can cause different fungal spore growth. Soil type is one of the factors that directly affect the presence of fungi. This research was conducted on the Wallace and Weber lines in Ternate, North Maluku. The research location was chosen because it has endemic fungal species, biodiversity that has not been widely discovered, and unique geographical conditions. Data collection was carried out through direct surveys using exploration methods, sampling with purposive random sampling, and direct collection of fungi based on shape, color, stem length, diameter, and type of substrate where they grow (soil, wood, leaves, and others), along with observations of fungal morphology. Qualitative analysis includes determining the order, family, genus, and scientific name presented in the form of tables and images, as well as descriptions of the characteristics of each species based on the identification results. The diversity index was also calculated. Environmental parameters measured included air temperature, soil moisture, light intensity, and soil pH. The results of the study showed that there were 20 species of fungi in the Moya Mabuku Hiking Trail Forest Area, Central Ternate District, Ternate City, North Maluku, Indonesia, with GPS coordinates of 0.8° North Latitude and 127.3630910° East Longitude. These fungi belong to the Ascomycota and Basidiomycota divisions, with the families Helotiaceae, Strophariaceae, Hygrophoraceae, Auriculariaceae, Omphalotaceae, Tremellaceae, Hypoxylaceae, Phyllotopsidaceae, Polyporaceae, Gardonemataceae, Tricholomataceae, Sarcoscyphaceae, Agaricaceae, Mycenaceae, Psathyrellaceae, and Cortinariaceae. The results of environmental parameter measurements on wood, soil, and coconut shell substrates showed that soil pH ranged from 3.85-6.10; air humidity 77.5-91.5% RH; substrate humidity 36.5-99.9%; Light intensity ranges from 93.5 to 7496 cd; air temperature ranges from 27.7 to 33.9°C; and substrate temperature ranges from 27.4 to 33.9°C. These pH conditions, ranging from 3.85 to 6.15, are considered optimal for supporting the growth of macroscopic fungi.